Preconditioning strategies to prevent acute kidney injury - Späth, Martin Richard (F1000Res, 2020)
Acute kidney injury is a common clinical disorder resulting in significantly increased morbidity and mortality. However, despite extensive research, strategies for prevention or treatment are still lacking in routine clinical practice. Already decades ago, several preconditioning strategies (e. g. ischemic/hypoxic preconditioning and calorie restriction) have been published and their extraordinary effectiveness - especially in rodents - has raised the hope for powerful clinical tools to prevent acute kidney injury. However, the underlying mechanisms are still not completely understood and translation to the clinics has not been successful yet. In this review, the most attractive strategies and the current mechanistic concepts are introduced and discussed. Furthermore, we present clinical trials evaluating the feasibility of preconditioning in the clinical setting.